A 300 GHz quasioptical schottky frequency doubler - Shalaan, M; Bozzi, M; Weinzierl, Jochen; Beilenhoff, K; Conciauro, G; Brand, Hans; Hartnagel, H (International Journal of Infrared and Millimeter Waves, 1997)
A monolithically integrated frequency multiplier based on a planar antenna providing impedance matching has been realized and measured at 300 GHz. Each of the two circuits comprises a Schottky varactor, slot antenna, MIM-capacitor and microstrip bias feed. The theoretical design aspects, the technological approach and the RF performance are addresse
lhft_intern.bib::thirty_years_LHFT_413